Bronchogenic cyst removal via thoracoscopic surgery in the prone position: A case report and literature review. (2019) - Ota, Yoshihiro; Watanabe, Takafumi; Takahashi, Kosuke; Suda, Takeshi; Tachibana, Shingo; Matsubayashi, Jun; Nagakawa, Yuichi; Osaka, Yoshiaki; Katsumata, Kenji; Tsuchida, Akihiko
Highlights: Bronchogenic cysts rarely arise from the diaphragm. Non-specific imaging features sometimes make a preoperative diagnosis difficult. An early diagnostic surgical excision is the most definitive method of management. Posterior mediastinal bronchogenic cysts can be excised thoracoscopically. Intraoperative prone positioning of the patient enhances the ease of this approach. Abstract: Introduction: Mediastinal bronchogenic cysts are encountered relatively often, but in many cases, diagnosis using imaging modalities, is difficult. Early surgical excision of bronchogenic cysts is recommended as a diagnostic and therapeutic measure. Here, we report the case of patient with a lower mediastinal bronchogenic cyst, who was treated using thoracoscopic surgery with prone positioning and include a review of literature on diagnosis and treatment of this condition. Presentation of case: The patient was a 66-year-old woman with an asymptomatic cystic lesion in the posterior, lower mediastinum. The lesion was diagnosed as an esophageal cyst using preoperative imaging and was scheduled for thoracoscopic removal with the patient in the prone position. Intraoperatively, the lesion was found to have no continuity with the esophageal wall and was easily separated from it. Moreover, a cord extending to the lesion, appeared to arise from the crura of the diaphragm. On histopathological examination of the extracted mass, the lesion was diagnosed as a bronchogenic cyst. Postoperatively, the patient recovered uneventfully and was discharged after 7 days. Conclusion: Thoracoscopic mediastinal cystectomy with the patient in the prone position may be an optimal surgical strategy for the treatment of bronchogenic cysts in the posterior, lower mediastinum.